Feasibility of on-farm reduction of nitrate pollution in subsurface drainage water - Hughes, Edmund John (Cranfield University, 1996)
Nitrate polluted water from agricultural drainage systems is currently treated by the water industry for mains supply. Moves towards a polluter pays policy resulting from European Union legislation and consumer pressure will, however, have major implications for the agricultural industry. The aim of this study was to identify, investigate and evaluate on-farm strategies for reducing nitrate pollution in subsurface drainage water. The high peaked nitrate rich discharges of drainflows from agricultural catchments in late autumn present significant management problems. One possibility which was examined is for polluting drainflows to be identified, intercepted and diverted into a holding pond or reservoir. Once stored, possible effective handling strategies include: long term storage, dilution, recirculation of the polluted water back onto the .land, and anaerobic treatment. Anaerobic treatment is a method of reducing nitrate to harmless nitrogen gas, however, lower temperatures in late autumn would suppress microbial activity, and possibly treatment performance. Further detailed laboratory study was carried out to assess the potential of anaerobic treatment during winter. Initially, the hypothesis that the nitrate concentration of drainage water could be reduced when applied to soil was tested, leading to the conclusion that it was only possible when a readily utilisable carbon source was continuously present. Glucose was added to water with a nitrate concentration of 1 00mg/1 and applied to soil columns. Complete reduction of nitrate concentration was achieved at 10°C, demonstrating the feasibility of anaerobic treatment during winter. The study also confirmed the optimum application ratio of glucose-carbon to nitrate-nitrogen as 1.65 to 1, and the environmental threshold as a redox potential of 200m V. Attached growth water treatment systems which utilise soluble carbon sources are, however, unsustainable because clogging of the porous media by microbial biomass results in hydraulic failure. The hypothesis that organic materials be used both as carbon source and the microbial growth site was tested. Provisional examination of the biodegradability of several organic materials demonstrated that sugar beet could upon degradation be a source of readily utilisable carbon. Sugar beet was subsequently used in small-scale laboratory based nitrate reducing water treatment systems. An average treatment performance of 23 grams of nitrate-nitrogen reduced per cubic metre of bio-reactor per day was achieved by maintaining a near neutral pH environment with the addition of crushed limestone. Clogging was not experienced and therefore flow rate was both sustainable and controllable. An empirical based model was developed to predict the required flow rate of drainage water through the bio-reactor for a specified nitrate concentration reduction, ammonia concentration, and redox potential. Examination of drainflow data enabled polluting drainflow volumes and their associated average nitrate concentrations to be quantified, to form the basis of .a design specification for the proposed on-farm strategies. Designs for each strategy were made and limitations on use identified. Approximate costs were calculated and compared to the cost of on-farm anaerobic treatment utilising methanol as the carbon source. This demonstrated that treatment strategies offer a capital cost saving due to reduced design storage capacities, however, operating costs and the additional management expertise required make them less attractive to the farmer. Dilution has potential in areas where excess winter rainfall exceeds 200mm, however, the volume of water that can be diluted is limited. Recirculation requires further investigation, but has potential in areas of low excess winter rainfall and high soil moisture deficits, and where irrigation equipment is already available. Long term storage satisfies all the requirements for on-farm suitability, and would provide an additional environmental benefit of on-farm water conservation, at a cost 25% greater than that for off-farm water treatment alone.